The Influence of Service Quality on the Company's Brand Image for the Sustainability of the Food and Beverage Business - Putra, Irfan Kharisma; Arif, Ahmad Bachtiar (PINISI Discretion Review, 2023)
Nowadays the food and beverage industry has developed rapidly, one of which is cafes. Cafe managers must pay attention to the quality of their service to make consumers satisfied with the service provided. Nendes Kombet (NK) is a cafe in Malang Regency which has a semi-outdoor concept with a natural atmosphere theme that can provide a sense of comfort to its visitors. Cafes can be manifested as companies because they both have a profit orientation. Companies are still required to build and maintain a good image even in various conditions. This effort is made by the company to improve the company's image and give consumers an impression about the services provided by the company. This research was conducted to determine the influence of service quality on the company's brand image for the sustainability of the food and beverage business carried out at NK Cafe Malang. This research uses a quantitative approach with a survey method to collect samples and uses a questionnaire as a data collection tool. The research results show that simultaneously and partially the variables of service quality consisting of tangible, reliability, responsiveness, assurance and empathy have a significant effect on the brand image variable. It is hoped that this research can be used as a reference in developing a business, especially the food and beverage industry.